Wife, mother, spy : an extraordinary life filled with ordinary days - Butler, Ann E., 1961- (AEB Associates LLC, 2024)
"Many mothers shuttle their kids to dance lessons and sports practice, coordinate playdates, read bedtime stories, and struggle to get dinner on the table after a long day at the office. Very few do all this while secretly meeting with spies, carrying a purse retrofitted to conceal a Glock, and tasked with protecting the security of the United States. For several decades, this was the life of Ann Butler--wife, mother of five, and operations operative for the CIA. From New York to Paris to Sarajevo, from Northern Africa to Central Europe, Wife, Mother, Spy provides a rare behind-the-scenes glimpse of the rewarding, chaotic, exhausting, often challenging, but always exciting life of a CIA spy who also happens to be a wife and mother. Juggling parenthood, aliases, transatlantic moves every few years with five children and a dog, and going into labor during a clandestine meeting isn't for the faint of heart. But with determination, a sense of humor, and unflappable optimism, Butler takes readers along on an inspiring journey that knits together a life full of the dailiness, hopes, and fears all parents share with an exhilarating career few can imagine." -- Page [4] cover.